Gyroid‐Structured 3D ZnO Networks Made by Atomic Layer Deposition. (3rd September 2013) - Kim, Ellie; Vaynzof, Yana; Sepe, Alessandro; Guldin, Stefan; Scherer, Maik; Cunha, Pedro; Roth, Stephan V.; Steiner, Ullrich
<x xml:space="preserve">Abstract</x> 3D continuous ZnO morphologies with characteristic feature sizes on the 10 nm length scale are attractive for electronic device manufacture. However, their synthesis remains a challenge because of the low crystallization temperature of ZnO. Here, we report a method for the robust and reliable synthesis of fully crystalline 3D mesoporous ZnO networks by means of atomic layer deposition (ALD) of ZnO into a self‐assembled block copolymer template. By carefully optimizing the processing conditions we are able to synthesize several‐micrometer‐thick layers of mesoporous ZnO networks with a strut width of 30 nm. Two 3D mesoporous morphologies are manufactured: a periodic gyroid structure and a random worm‐like morphology. Exploiting the ALD property to conformally coat complex surfaces of high aspect ratio, the channel network of a 3D continuous channel network of a self‐assembled block copolymer is replicated into ZnO. X‐ray photoemission spectroscopy and x‐ray diffraction measurements reveal that the chemical composition of the mesoporous structures is uniform and consists of wurtzite‐ZnO throughout the film. Scanning electron microscopy reveals an average pore dimension of 30 nm. The potential of this material for a hybrid photovoltaic application is demonstrated by the manufacture of a poly(3‐hexylthiophene)/ZnO solar cell.